Mapeamento dos produtos e serviços tecnológicos na Universidade Federal do Tocantins – UFT - Costa, Beatriz Batista (UFT, 2021)
This study aimed to map the technological products and services developed and offered by the Federal University of Tocantins - UFT, to relate to the following industrial studies published in the State of Tocantins. The method used in the research was exploratory, within the qualitative approach, using a semi-structured questionnaire. For the composition of the information, documentary analysis and information from secondary sources was also used, such as the data available from the National Institute of Industrial Property - INPI. The results showed that the technologies developed in the UFT laboratories on the Araguaína, Palmas and Gurupi campus are gradually growing, however the interaction of services is allowed with companies is still timid. It was found that most UFT laboratories are focused only on teaching; in the other verified laboratories, it does not refer to innovation in products / services, as incremental innovations represent 95%, with only 5% of radical innovations. Regarding the mapping of technologies that have software records, check if the majority of software records do not exist in the Generic IF-10 (data processing) field, concentrating a larger volume of records. Through this mapping, it was possible to verify that the areas with the most patents are in the chemical, petrochemical and pharmaceutical industry, construction industry and food industry. In the research or product development laboratories, it has been growing gradually, as there are investments, equipment and infrastructure produced with few services and technological products. However, it draws attention or low level of articulation between laboratories and companies in the state, being the biggest discussion on U-E interaction. The study resulted in the construction of a technological portfolio that clearly presents technologies in products and services provided by the Federal University of Tocantins-UFT. Believe that this can be a strategic tool to assist managers in the area of innovation in trying to interact with the productive sector and also without developing institutional policies for entrepreneurship and innovation